B-Cell Activating Factor Predicts Acute Rejection Risk in Kidney Transplant Recipients: A 6-Month Follow-Up Study - Wang, Xu-Zhen; Wan, Zhen; Xue, Wu-Jun; Zheng, Jin; Li, Yang; Ding, Chen Guang (Frontiers in Immunology, 2019)
B cell activating factor (BAFF) belonging to TNF family is a cytokine that enhances B-cell proliferation and differentiation. Recently, It has been suggested that BAFF might be a potential therapeutic target for treating autoimmune disease. However, the relationship between BAFF and allograft rejection has not been determined. Based on the results from previous studies, we conducted a six-month follow-up study to confirm the hypothesis that BAFF might be a risk factor for predicting acute rejection in kidney transplant recipients. A total of 155 kidney transplant recipients were recruited from October 2015 to October 2017. We found that the serum BAFF level was 2426.19 ± 892.19 pg/mL (95% confidence interval: 1489.89 3362.49 pg/ml) at the time of acute rejection, significantly higher than that in the stable renal function group (988.17 ± 485.63 pg/mL, P< 0.05). In addition, BAFF expression was significantly enhanced in the membrane and cytoplasm of renal tubule epithelial cells in the transplant kidney tissue with acute rejection, which also had a positive correlation between BAFF and C4d expression in transplanted kidney tissues (r = 0.880, P = 0.001). Kaplan-Meier survival analysis showed that recipients with higher pretransplant BAFF levels had higher acute rejection incidence (P=0.003). In conclusion, we have identified that BAFF levels are associated with pre-transplant sensitization and are useful in predicting kidney transplant rejection.